Enterococcus faecium genome dynamics during long-term asymptomatic patient gut colonization - Bayjanov, Jumamurat R.; Baan, Jery; Rogers, Malbert R.C.; Troelstra, Annet; Willems, Rob J.L.; van Schaik, Willem (Microbiology Society, 2019)
Enterococcus faecium is a gut commensal of humans and animals. In addition, it has recently emerged as an important nosocomial pathogen through the acquisition of genetic elements that confer resistance to antibiotics and virulence. We performed a whole-genome sequencing-based study on 96 multidrug-resistant E. faecium strains that asymptomatically colonized five patients with the aim of describing the genome dynamics of this species. The patients were hospitalized on multiple occasions and isolates were collected over periods ranging from 15 months to 6.5 years. Ninety-five of the sequenced isolates belonged to E. faecium clade A1, which was previously determined to be responsible for the vast majority of clinical infections. The clade A1 strains clustered into six clonal groups of highly similar isolates, three of which consisted entirely of isolates from a single patient. We also found evidence of concurrent colonization of patients by multiple distinct lineages and transfer of strains between patients during hospitalization. We estimated the evolutionary rate of two clonal groups that each colonized single patients at 12.6 and 25.2 single-nucleotide polymorphisms (SNPs)/genome/year. A detailed analysis of the accessory genome of one of the clonal groups revealed considerable variation due to gene gain and loss events, including the chromosomal acquisition of a 37 kbp prophage and the loss of an element containing carbohydrate metabolism-related genes. We determined the presence and location of 12 different insertion sequence (IS) elements, with ISEfa5 showing a unique pattern of location in 24 of the 25 isolates, suggesting widespread ISEfa5 excision and insertion into the genome during gut colonization. Our findings show that the E. faecium genome is highly dynamic during asymptomatic colonization of the human gut. We observed considerable genomic flexibility due to frequent horizontal gene transfer and recombination, which can contribute to the generation of genetic diversity within the species and, ultimately, can contribute to its success as a nosocomial pathogen.
Keywords: Accessory genome; Enterococcus faecium; Gut colonization; Insertion sequences; Microbial evolution; Epidemiology; Microbiology; Molecular Biology; Genetics